Everyday information practices of ethnic minorities with small populations in Yunnan, China - Zhu, Ming; Liao, Xizhu (Malaysian Journal of Library and Information Science, 2021)
This paper explores the everyday information practices of ethnic minorities with small populations (EMSP) to identify the conditions that affect their information practices within the context of Chinese culture. A qualitative study was conducted with China’s ethnic minorities, and data were collected through in-depth interviews and observations involving 45 participants. The data were statistically analyzed and processed using three levels of qualitative data coding analysis to identify the conditions that affect their everyday information practices. Findings show that the information needs of EMSP in China are relatively centralized, their sources of information acquisition are relatively fixed, and they do not cross ethnic group boundaries to share information with the outside world. In addition, traditions, customs, lifestyle, and ethnic identity are the conditions that influenced their everyday information practices. These results further the understanding of ethnic characteristics and traditional culture as conditions that can influence everyday information practices.